Government and Private Cooperation in Infrastructure Development Case Study in Makassar City Toll Road Development - Nurcitra; Paddu, Abd Hamid; Razak, Abd Rahman (Economics and Business Journal (ECBIS), 2023)
The purpose of this study is to investigate how the public-private partnership model based on the construction-operation-transfer model in the case of infrastructure development in Makassar City is utilized in the construction of the Makassar City Toll Road. After satisfying the requirements set in each case, a public-private partnership contract is concluded. The construction of toll roads is basically done by the government, the Ministry of Public Affairs and a corporate body (in this case PT Bosova Margautama Nusantara) using a build-operate-transfer model (generally a model involving two parties). is constructed by public service users, governments, and service providers are involved in building and operating the infrastructure. After granting the right of use for 35 years as the organizer, it will be handed over to the government after the concession period.